Peran LAZISMU Medan Dalam Meningkatkan Kesejahteraan Masyarakat:Pemahaman, Dan Dampak Positif Lazismu Bagi Masyarakat - Anggi Maharani Nasution; Imsar Imsar (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to explore the role of Lazismu Medan City in improving community welfare as well as the positive impact felt by the community. This research explores Lazismu's various contributions, with the aim of providing an understanding of Lazismu and its positive impact on community welfare. Through a thorough analysis of Lazismu's functions, this research intends to provide insight into effective approaches for sustainable community development. The research method used is a qualitative method with a case study approach. Data was collected through in-depth interviews, participatory observation, document analysis related to LAZISMU Medan activities, and literature study. Research respondents involved LAZISMU management, donors, and beneficiary communities. The results showed that LAZISMU Medan has an important role in collecting and distributing zakat, infaq, and alms. Various programs have been implemented, such as assistance for education, economic empowerment efforts, health support, and other social assistance programs. The positive impact of these programs is reflected in increased access to education, community economic growth, and improved health and social welfare.